METAFORA DALAM ANTOLOGI PUISI HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO: KAJIAN METAFORA GEORGE LAKOFF - Hajri Faisal, Nurul Annisa; Hajrah, Hajrah; Abidin, Aslan (Fakultas Bahasa dan Sastra Indoensia, 2025)
This study aims to analyze metaphors in the anthology of the poem Hujan Bulan Juni by Sapardi Djoko Damono using Lakoff's metaphor theory. The data is sourced from the poetry anthology book Rain in June by Sapardi Djoko Damono. The focus of this research is things related to metaphors and new meanings. The type of research carried out is qualitative research that is descriptive to describe personification, new methodologies and meanings. The results of the study show that in the anthology of the poem Hujan Bulan Juni by Sapardi Djoko Damono there is a personification that includes: It likens Wind as a figure who interacts with nature, Flowers and Numbers as a beautiful but complex female attitude, Sweets as the sweet beauty of women, Life as a teacher who gives lessons, and Chill as an emotional experience experienced. Then there is the metonymy which includes: the word Rain which refers to a quiet atmosphere, the word Rose which refers to the beauty of a woman, the word Train which refers to the hope of a future that continues to advance, the word Ear which refers to someone who wants to be heard more deeply, and the word Heaven which refers to the form of eternity. Then there is a new meaning that the author gets in this poem which is connotation with a deep meaning as follows: the word Rain in a connotative meaning (new meaning) as a hope of change and a denotative meaning as rain that comes on time, the word Tomb in a connotative meaning (new meaning) as a life behind the silence of the tomb and a denotative meaning as a crowded night even though there is no sound, the word Paper in a connotative meaning (new meaning) as the creativity of children and the denotative meaning as the imagination of children, the word grudge in the connotative meaning (new meaning) as the growth of feelings of resentment in a person and the denotative meaning as the grudge conceived and produced by humans. Therefore, it can be concluded that poets use metaphors and new meanings in their poems.